Development and validation of PCR-based assays for diagnosis of American cutaneous leishmaniasis and identificatio nof the parasite species - Grazielle Cardoso da Graça; Angela Cristina Volpini; Gustavo Adolfo Sierra Romero; Manoel Paes de Oliveira Neto; Marcia Hueb; Renato Porrozzi; Mariana Côrtes Boité; Elisa Cupolillo (Memorias do Instituto Oswaldo Cruz, 2012)
In this study, PCR assays targeting different Leishmania heat-shock protein 70 gene (hsp70) regions, producing fragments ranging in size from 230-390 bp were developed and evaluated to determine their potential as a tool for the specific molecular diagnosis of cutaneous leishmaniasis (CL). A total of 70 Leishmania strains were analysed, including seven reference strains (RS) and 63 previously typed strains. Analysis of the RS indicated a specific region of 234 bp in the hsp70 gene as a valid target that was highly sensitive for detection of Leishmania species DNA with capacity of distinguishing all analyzed species, after polymerase chain reaction-restriction fragment length polymorfism (PCR-RFLP). This PCR assay was compared with other PCR targets used for the molecular diagnosis of leishmaniasis: hsp70 (1400-bp region), internal transcribed spacer (ITS)1 and glucose-6-phosphate dehydrogenase (G6pd). A good agreement among the methods was observed concerning the Leishmania species identification. Moreover, to evaluate the potential for molecular diagnosis, we compared the PCR targets hsp70-234 bp, ITS1, G6pd and mkDNA using a panel of 99 DNA samples from tissue fragments collected from patients with confirmed CL. Both PCR-hsp70-234 bp and PCR-ITS1 detected Leishmania DNA in more than 70% of the samples. However, using hsp70-234 bp PCR-RFLP, identification of all of the Leishmania species associated with CL in Brazil can be achieved employing a simpler and cheaper electrophoresis protocol.